Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13014-022-01987-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative lymphatic recurrence distribution and delineation of the radiation field in lower thoracic squamous cell esophageal carcinomas: a real-world study

Abstract: Background To study lymphatic recurrence distribution after radical surgery in the real world and guide clinical tumor volume delineation for regional lymph nodes during postoperative radiotherapy for lower thoracic squamous cell esophageal carcinomas. Methods We enrolled patients who underwent radical esophagectomy, without radiation before or after surgery, at 3 cancer hospitals. Patients were classified into groups according to tumor locations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Based on our previous real-world study [ 22 ], the recurrence patterns could be slightly different in practice, and the number of recurrent lymph nodes could influence the prognosis of patients. Comprehensive treatment, including surgery and postoperative radiotherapy, not only influenced the prognosis of patients but also the patterns of lymphatic recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous real-world study [ 22 ], the recurrence patterns could be slightly different in practice, and the number of recurrent lymph nodes could influence the prognosis of patients. Comprehensive treatment, including surgery and postoperative radiotherapy, not only influenced the prognosis of patients but also the patterns of lymphatic recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, the hospitals we chose were all large centres located in central China, where was representative of high incidence of oesophageal carcinomas in China [ 25 ], hence, the results of this study could represent the classical characteristics of oesophageal cancer in our country. And this study, as a sequential study of real-world research on lower thoracic oesophageal carcinomas [ 22 ], depicted the recurrence patterns of middle thoracic carcinomas and the high-risk prognostic factors of lymphatic metastasis. The recurrence patterns of carcinomas in the two different locations suggested that there were detailed differences in the frequency of recurrence in para-oesophageal and celiac lymph nodes, but both studies showed a high recurrence rate in the supraclavicular station.…”
Section: Discussionmentioning
confidence: 99%